Circulating Tumor Cells: Magnetic "Squashing" of Circulating Tumor Cells on Plasmonic Substrates for Ultrasensitive NIR Fluorescence Detection (Small Methods 2/2019). Issue 2 (12th February 2019) - Zhang, Ru; Le, Biao; Xu, Wei; Guo, Kai; Sun, Xuming; Su, Haiyang; Huang, Lin; Huang, Jingyi; Shen, Ting; Liao, Tao; Liang, Yongye; Zhang, John X. J.; et al.
Abstract : In article number1800474, John X. J. Zhang, Hongjie Dai, Kun Qian, and co‐workers, demonstrate that magnetic 'squashing' of circulating tumor cells (CTCs) on plasmonic substrates is achieved for ultrasensitive near‐infrared (NIR) fluorescence detection. Owing to the squashing of cells by magnetic forces and the resulting close proximity of NIR labels on cells to the plasmonic surface, an ultrahigh NIR fluorescence enhancement of ≈50–120 fold is observed, drastically enhancing the ability of CTC detection, imaging, and analysis.